Hypotension aggravated by dopamine in a dog under isoflurane anesthesia - Carvalho, Elizabeth Regina [UNESP]; Garofalo, Natache Arouca [UNESP]; Girotto, Carolina Hagy [UNESP]; Teixeira Neto, Francisco José [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: Hypotension (MAP < 60 mmHg) is the most common complication in anesthetic practice and has been identified in 38% of canine patients undergoing general anesthesia for variety of procedures. Normalization of arterial pressure can usually be achieved by decreases in inhalant anesthetic concentrations, fluid administration, and use of inotropes/ vasopressors in healthy animals (ASA I) or animals with mild systemic disease (ASA anesthetic risk II). The present report shows an ASA II dog with severe hypotensive crisis [mean arterial pressure (MAP) < 50 mmHg] during general anesthesia, in which the procedure was aborted because hypotension was aggravated by dopamine. Case: A 7-year-old male Bull Terrier was anesthetized for magnetic resonance imaging (MRI) of a tumor in the face. After intramuscular acepromazine (0.01 mg/kg) and meperidine (3 mg/kg), anesthesia was induced with intravenous (IV) ketamine (1 mg/kg) and propofol (2.3 mg/kg) and maintained with isoflurane in oxygen. Ten min after induction of anesthesia MAP was 45 mmHg, while end-tidal isoflurane (ETISO) concentration was 0.5%. End-tidal isoflurane was decreased to 0.3% and an IV bolus of Lactated Ringer's was initiated (15 mL/kg over 10 min), followed by two ephedrine boluses (0.1 mg/kg, IV) administered 5 min apart. MAP remained low (< 50 mmHg) and dopamine constant rate infusion (CRI) was initiated (7.5 μg/kg/min). Ten minutes after dopamine CRI was commenced, MAP was further decreased to 25-22 mmHg. Dopamine CRI was increased to 10 μg/kg/min, but MAP remained < 25 mmHg. Infusion drugs and isoflurane anesthesia were stopped. After the animal was extubated MAP returned 60-70 mmHg. Discussion: Among the drugs used, isoflurane is known for decreasing blood pressure in a dose-related manner because of its vasodilating properties. Hypotension is rarely associated with low end-tidal isoflurane concentrations (0.3-0.5%) in animals that do not present previous evidence of circulatory dysfunction. Acepromazine may have contributed to the hypotensive actions of isoflurane in the case reported here because of its vasodilating effects. Acepromazine has prolonged plasma half-life (7 h) and might also have contributed to the lack efficacy of ephedrine to treat hypotension. Aggravation of hypotension (MAP decreased from 45-50 mmHg to approximately 25 mmHg) by dopamine was unexpected. Aggravation of hypotension during administration of vasopressor doses of dopamine could be related to the activation of the cardiopulmonary chemoreflex (CCR), previously known with the eponym Bezold-Jarisch reflex or due to a prevalence of dopamine´s vasodilatory effects (dopaminergic receptor stimulation) and failure of this drug in promiting increased CO and SVR at the dose ranges used (7.5 to 10 μg/kg/min).. The CCR involves activation of mechano and baroreceptors in the heart, by inotropes such as dopamine and dobutamine. This activation originates vagal afferent impulses to the nucleus tractus solitarii of the spinal cord, which in turn originates parasympathetic afferent impulses to the heart. The consequence is an increase in parasympathetic outflow and decreased sympathetic activity, ultimately producing bradycardia, hypotension, or both.
Keywords: Acepromazine; Bezold-Jarish reflex; Canine; Cardiopulmonary chemoreflex; Inotropes